2020
DOI: 10.3390/cancers12030546
|View full text |Cite
|
Sign up to set email alerts
|

Association of Steroids Use with Survival in Patients Treated with Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Immune checkpoint inhibitors (ICIs) can elicit toxicities by inhibiting negative regulators of adaptive immunity. Sometimes, management of toxicities may require systemic glucocorticoids. We performed a systematic review and meta-analysis of published studies to evaluate the correlation between steroids use, overall survival (OS), and progression-free survival (PFS) in cancer patients treated with ICIs. Publications that compared steroids with non-steroid users in cancer patients treated with ICIs from incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 43 publications
3
181
0
3
Order By: Relevance
“…The systemic administration of synthetic glucocorticoids such as dexamethasone and prednisolone has been associated with poorer outcomes in patients with ICI-treated cancer. 8 It has been shown that both synthetic and endogenous glucocorticoids can inhibit anticancer immune response through an impairment of the antigen presentation by dendritic cells or the activation of T-cells. 9 Given that endogenous glucocorticoids is produced by the adrenal glands, one might hypothesize the adrenal gland microenvironment might be immunosuppressive and acts as a sanctuary site for ICI-treated neoplasms tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic administration of synthetic glucocorticoids such as dexamethasone and prednisolone has been associated with poorer outcomes in patients with ICI-treated cancer. 8 It has been shown that both synthetic and endogenous glucocorticoids can inhibit anticancer immune response through an impairment of the antigen presentation by dendritic cells or the activation of T-cells. 9 Given that endogenous glucocorticoids is produced by the adrenal glands, one might hypothesize the adrenal gland microenvironment might be immunosuppressive and acts as a sanctuary site for ICI-treated neoplasms tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis explored the impact of steroids across 16 studies with melanoma and NSCLC patients [ 16 ]. Overall, the patients treated with steroids had a higher risk of both progression and death, but only the intercurrent steroids for palliative purposes were related to the greater risk of death compared to patients receiving steroids for brain metastasis or irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study showed that the patients who received prednisone >10 mg at the start of immunotherapy had a shorter median OS than those who received 0-10 mg of prednisone (4.9 vs. 11.2 months) (42). However, a recent meta-analysis pointed out that the use of steroids to mitigate adverse events did not negatively affect OS (43). Moreover, some studies showed that the use of antibiotics often leads to worse treatment response and OS in patients treated with ICIs (44,45).…”
Section: Clinical Managementmentioning
confidence: 99%